A Comprehensive Review of Lubricant Chemistry, Technology, Selection, and Design - Rizvi, Syed Q. A. (USA ASTM International, 2009)
Get a comprehensive overview of lubricant technology and its use in formulating new lubricants. This unique, new ASTM manual is written from the perspectives of both chemists and lubrication engineers, and therefore places equal emphasis on the chemistry and the formulation of lubricants. In addition it includes additive technology that is used in petroleum exploration, refining, and fuels. A Comprehensive Review of Lubricant Chemistry, Technology, Selection, and Design complements ASTM's Fuels and Lubricants Handbook in that it integrates the information in the Handbook in a manner that will be especially useful to practicing lubrication engineers.
Includes Illustrations and Index.
Keywords: Lubricating oils